UDIMA's EPBE Project, a boost for the employability of young european people - Sara Delgado Resino; Ana Landeta Etxeberria; Silvia Nazareth Prieto Preboste (Centro de Estudios Financieros, 2017)
The European Personal Branding for Employment (EPBE) is a project subsidised by the Erasmus+ Programme, specifically in Key Action 2: «Cooperation for the innovation and exchange of good practices». UDIMA concludes the EPBE Project this september, which was implemented in partnership with other institutions, in particular, universities, training centres and companies in Italy, Greece, Germany, Cyprus and Spain. The aim of the project was to encourage employment among young people through the acquisition of digital skills. The beneficiaries are not only young people from the European Union, students of higher education and professional training, but also jobseekers, teachers belonging to participating institutions and other interested trainers, including those who wanted to improve their references and increase their employability. In order to achieve this objective, UDIMA and the other participating institutions have used innovative pedagogical methods and generated a large number of open educational resources, including a training course for teachers and two massive online open courses (MOOCs) available in UDEMY Platform. The article describes the resources and results produced within the framwork of this project.